Hemorheological system in coronary heart disease patients: prognostic value - L. I. Malinova; P. Yu. Dovgalevsky (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To develop highly sensitive prognostic methods for coronary heart disease (CHD) and acute coronary event (ACE) risk stratification, on the basis of biophysical hemorheological system assessment. Material and methods. Seven-year follow-up data on CHD patients were analyzed: re-hospitalization rate and reasons; main hemorheological parameters, their temporal and velocity characteristics; hemorheological system modeling by creating phase fragments in multi-dimensional phase space. Results. Whole blood viscosity was significantly higher in patients with 3 or more ACE, comparing to ACE-free individuals or participants with <3 ACE. Velocity parameter dynamics correlated with ACE hospitalization rate. Phase fragment method demonstrated hemorheological system destabilization, maximal in patients with 3 or more ACE. Conclusion. Prognostic value of whole blood viscosity and velocity assessment was demonstrated in CHD patients. Various CHD therapy algorithms, depending on hemorheological parameters and ACE risk, were developed.